TECHNOLOGY OF PRODUCTION OF HIGH-STRENGTH REINFORCING STEEL - A. N. Bondarenko; V. I. Shcherbakov; G. L. Bobrenok; A. E. Chernov (Литьë и металлургия)
The technology of the high-strength spiral hardware is considered in the article. The offered technology allows to bring the mechanical characteristics of high-strength reinforcing steel to conformity with the requirements of practically all the well-known in world practice standards on such kind of production.